Using KDamper for Seismic-Induced Vibration Mitigation of Wind Turbines - Pan, Xunyi (Curtin University, 2024)
This study explores the effectiveness of a novel vibration control device, KDamper, in mitigating vibrations in wind turbine towers. Compared to traditional methods like TMDs, KDamper shows superior performance in reducing displacement and acceleration responses under various seismic conditions. The findings suggest that KDamper offers a promising solution for enhancing the structural safety and functionality of wind turbines.